Identifying effective mechanisms to assist the marketing integration process for Malaysian acquirers - Jedin, Mohd. Haniff; Md Saad, Norsafinas (College of Business, National Taipei University, 2012)
Marketing integration in mergers and acquisitions (M&As) is an important means of ensuring the survival of the combined firm.This can be achieved by streamlining and redeploying all marketing resources from both sides: the acquirer and the acquired firm.Marketing integration could be referred to as the backbone of the firm combining process because of its potential to generate higher revenues for the newly-combined firm. However, existing studies have not clearly investigated the mechanisms that contribute to the marketing integration process in cross-border M&As.The purpose of this study was to fill this gap by exploring effective mechanisms that can improve this process.Specifically, marketer collaboration, interaction, marketing synergy, and the redeployment of marketing resources were proposed as key mechanisms that influence marketing integration in this context.The results indicated that marketing synergy and the redeployment of marketing resources have a strong and significant impact on the extent of integration.Meanwhile, there is a striking negative and significant result that pertains to the relationship between interaction and speed of integration.